ADMINISTRATIVE ACTIVITY OF HEADS OF EDUCATIONAL INSTITUTIONS IMPROVEMENT (American Journal of Interdisciplinary Research and Development, 2023)
This article which is for educational management and educational institution leaders highlights the importance of developing management competence. This is education problems related to the management and development of the educational system in institutions is an article written about theoretical and practical issues to be solved. In the article, there are more details provided on the skills and knowledge required for leaders, and this knowledge improves the educational process and improves the quality of education in the educational institution.